2005
DOI: 10.1097/01.ccm.0000186745.53059.f0
|View full text |Cite
|
Sign up to set email alerts
|

Fresh frozen plasma transfusion in critically ill medical patients with coagulopathy*

Abstract: The risk-benefit ratio of FFP transfusion in critically ill medical patients with coagulopathy may not be favorable. Randomized controlled trials evaluating restrictive vs. liberal FFP transfusion strategies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
116
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(126 citation statements)
references
References 17 publications
5
116
1
4
Order By: Relevance
“…9 Recent studies suggested that abnormal coagulation blood tests including an elevated international normalized ratio or activated partial thromboplastin time are common in the critically ill, 9,61,62 and administration of FFP is neither effective in correcting these abnormal coagulation results nor necessarily able to prevent clinical bleeding. 62,63 Whole blood VE-POC tests, including thromboelastography (Teg ® ; Haemonetics ® , Braintree, MA, USA) and rotational thromboelastometry (Rotem ® ; The Tem Group, Basel, Switzerland), are increasingly used to guide FFP (and other blood products) transfusion in the perioperative and critical care settings.…”
Section: Benefits and Risks Of Ffp Transfusions In The Critically Illmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Recent studies suggested that abnormal coagulation blood tests including an elevated international normalized ratio or activated partial thromboplastin time are common in the critically ill, 9,61,62 and administration of FFP is neither effective in correcting these abnormal coagulation results nor necessarily able to prevent clinical bleeding. 62,63 Whole blood VE-POC tests, including thromboelastography (Teg ® ; Haemonetics ® , Braintree, MA, USA) and rotational thromboelastometry (Rotem ® ; The Tem Group, Basel, Switzerland), are increasingly used to guide FFP (and other blood products) transfusion in the perioperative and critical care settings.…”
Section: Benefits and Risks Of Ffp Transfusions In The Critically Illmentioning
confidence: 99%
“…6,7 In the latest audit of our critically ill patients, up to 27% of the ICU patients still received allogeneic RBC transfusions, especially common in those with multiple organ failure, despite adopting a restricted transfusion protocol. 8 Similarly, FFP (30%) and platelet (23%) transfusions remain common in the critically ill. 9,10 The findings of these epidemiological studies are not entirely surprising, because for better or worse, the clinical intuition to correct severely deranged physiology, such as anemia, or coagulation parameters before invasive procedures for someone who is also unwell in many other ways, is compelling. [9][10][11] Numerous studies assessing the benefits and risks of RBC and blood product transfusions have been published in the past few decades, but which and when patients should receive allogeneic blood products remain contentious and uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, massive transfusion based on a more physiologic regime resembling whole blood will improve survival. With reference to good results in several studies a new international consensus has been developed: A ratio of 1:1:1 in PRBC:FFP:PLT is advocated [9,[20][21][22]. This ratio results in decreased mortality, less blood products needed and decreased costs per patient.…”
Section: Massive Transfusion Of Blood Productsmentioning
confidence: 99%
“…Терапия концентратом АТ, хотя и связана с повы шенным риском геморрагических осложнений при сеп сисе [9], может снизить летальность при ДВС синдроме [10], в то время как введение СЗП сопровождается меньшим риском кровотечения, но может вызвать дру гие осложнения у пациентов, находящихся в критичес ком состоянии (ухудшение дыхательной функции у па циентов с сепсисом вследствие острого повреждения легких, риск анафилактических реакций, гемотрансфу зионных конфликтов, передачи инфекции) [11][12][13]. Планируя наше исследование, мы попытались ответить на вопрос о сравнительной эффективности СЗП и кон центрата АТ для коррекции дефицита АТ у пациентов с ДВС синдромом.…”
unclassified